2017
DOI: 10.1002/mgg3.278
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide genetic analysis for molecularly unresolved cystic fibrosis patients in a multiethnic society: implications for preconception carrier screening

Abstract: BackgroundPreconception carrier screening for cystic fibrosis (CF) is usually performed using ethnically targeted panels of selected mutations. This has been recently challenged by the use of expanded, ethnically indifferent, pan‐population panels. Israel is characterized by genetically heterogeneous populations carrying a wide range of CFTR mutations. To assess the potential of expanding the current Israeli preconception screening program, we sought the subset of molecularly unresolved CF patients listed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…No mutations were found in 12 (4.8%) patients. Studies from Iran and Israel utilizing the same methods revealed similar mutation detection rates of 81.9% and 89.3%, respectively . A study conducted in Syria revealed that 78% of the total mutations were detectable.…”
Section: Discussionmentioning
confidence: 99%
“…No mutations were found in 12 (4.8%) patients. Studies from Iran and Israel utilizing the same methods revealed similar mutation detection rates of 81.9% and 89.3%, respectively . A study conducted in Syria revealed that 78% of the total mutations were detectable.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive analysis of the possible effect of this insertion in the MutationTaster program was positive for pathogenicity. As a class I mutation, it leads to complete or near-complete loss of CFTR activity [12,40]. Even with complete sequencing of CFTR, 12 patients were identified with only one CFTR variant.…”
Section: Discussionmentioning
confidence: 99%
“…All patients underwent molecular analysis for the 15 most common mutations in Israel including Q359K/T360K, and CFTR Sanger sequencing when the mutation panel was negative [7]. Patients with ≥1 Q359K/T360K mutation meeting diagnostic criteria for CF [8] were included.…”
Section: Clinical Phenotypementioning
confidence: 99%